Future Trends in Obolodiplosis robiniae Distribution across Eurasian Continent under Global Climate Change - Jia-Qiang Zhao; Tai Gao; Jing-Jing Du; Juan Shi (Insects, 2023)
Obolodiplosis robiniae was discovered in Eurasia at the beginning of the 21st century. In this study, we explore the present and future (in the years 2050 and 2070) trends in the potential distribution of O. robiniae in Eurasia under diverse climate change scenarios based on a maximum entropy model. Our findings indicated that the current potential distribution area of O. robiniae is within the range of 21°34′ and 65°39′ N in the Eurasian continent. The primary factor controlling the distribution of O. robiniae is temperature. The highly and moderately suitable areas are mainly distributed in the semi-humid and semi-arid regions, which also happen to be the locations where the host black locust (Robinia pseudoacacia L.) grows at its fastest rate. The forecast of the potential distribution area of O. robiniae revealed that the species would benefit from global warming. The region suitable for the habitat of O. robiniae is characterized by a large-scale northward expansion trend and an increase in temperature. This information would help the forestry quarantine departments of Asian and European countries provide early warnings on the probable distribution areas of O. robiniae and provide a scientific basis for the prevention and control of O. robiniae spread and outbreaks.